Invasive Alien Species A New Synthesis. - Mooney, Harold A. (SCOPE Series., 2013)
Invasive alien species are among today's most daunting environmental threats, costing billions of dollars in economic damages and wreaking havoc on ecosystems around the world. In 1997, a consortium of scientific organizations including SCOPE, IUCN, and CABI developed the Global Invasive Species Programme (GISP) with the explicit objective of providing new tools for understanding and coping with invasive alien species. Invasive Alien Species is the final report of GISP's first phase of operation, 1997-2000, in which authorities from more than thirty countries worked to examine invasions as a worldwide environmental hazard. The book brings together the world's leading scientists and researchers involved with invasive alien species to offer a comprehensive summary and synthesis of the current state of knowledge on the subject. Invasive alien species represent a critical threat to natural ecosystems and native biodiversity, as well as to human economic vitality and health. The knowledge gained to date in understanding and combating invasive alien species can form a useful basis on which to build strategies for controlling or minimizing the effects in the future. Invasive Alien Species is an essential reference for the international community of investigators concerned with biological invasions.